Effects of De‐Icing Products on Putting Green Turf. Issue 1 (19th October 2017) - Hollman, A. B.; Heineck, G. C.; Frank, K. W.; Bauer, S. J.; Bryan, J.; Horgan, B. P.
Abstract : Prolonged ice cover of putting greens can lead to turfgrass crown death. De‐icing products can aid in ice removal, but variations in ice thickness and putting green topography increase the likelihood these products will contact and damage ice‐free turfgrass areas. The objective of this research was to assess, in two separate trials, the phytotoxic effect of chemical de‐icers and the greening effect of solar de‐icers applied directly to ice‐free creeping bentgrass ( Agrostis stolonifera L.) native soil and sand‐based putting greens. The chemical de‐icing trial included 11 products applied at rates of 136.3 and 68.2 g m −2 for all chemicals with the exception of sodium acetate, for which the label dictated rates of 136.3, 97.6, 73.2, 48.8, and 24.4 g m −2 were applied. The solar de‐icing trial contained nine products applied at a dry volume of 0.3 L m −2 to account for differences in bulk density. In 2014, only urea‐based de‐icing chemicals were damaging to the turf. In 2015, damage was seen by all de‐icing chemicals with urea‐based chemicals having the most severe damage; warm temperatures and thawed soil likely led to actively growing tissue encountering de‐icing chemicals and increasing the severity of the damage. Organic‐based fertilizers, categorized as solar de‐icing products, produced the greatest increase in green color in both years of the trial. Proper selection of chemical and solar de‐icing products, along with application timing, can limit damage to ice‐free bentgrass greens.